Perfil epidemiológico da raiva na região Noroeste do Estado de São Paulo no período de 1993 a 2007 - Queiroz, Luzia Helena [UNESP]; de Carvalho, Cristiano [UNESP]; Buso, Daniel Sartori [UNESP]; de Lucca Ferrari, Clara Isabel; Pedro, Wagner André [UNESP] (Soc Brasileira Medicina Tropical, 2009)
The epidemiology of animal rabies in the region of Aracatuba, in the northwest of São Paulo State, from 1993 to 2007, is described according to the results from diagnoses made at laboratories in the region, using the fluorescent antibody and mouse inoculation tests. Out of 10,579 samples analyzed, 4.9% were positive (518/10,579). Dogs accounted for 67% of the cases (346/518) and these occurred between 1993 and 1997. Among the other positive samples, 16% (84/518) were in cattle and 9.7% (50/518) were in bats. Among the 42 municipalities in the region, 23 (55%) presented at least one rabies-positive case, while 13 of them had cases in bats. Three distinct cycles of rabies were identified in the northwestern region of the State of São Paulo: the urban cycle characterized predominantly by canine rabies (1993 to 1997); and the aerial and rural cycles starting in 1998, with predominance of cases in bats in urban areas and in herbivores.
Epidemiological profile of rabies in the northwestern region of São Paulo State, from 1993 to 2007
Keywords: Rabies; Epidemiology; Laboratory diagnosis; Bats; Chiroptera